Vibration characteristics study of bladed disk assemblies - Jiang, Hong (2009)
Since most failures of rotating turbomachinery are caused by fatigue of their critical components - bladed disks, it is necessary to study the vibration characteristics of bladed disk assemblies in order to contribute to the successful operation of turbomachinery. This research is intended to investigate the vibration characteristics of tuned and mistuned bladed disk assemblies by both theoretical and experimental approaches, so that the vibration characteristics of bladed disk assemblies can be predicted accurately, and the obtained results can provide theoretical guidance for practical use.